An evidence map of yoga for low back pain. (April 2016) - Goode, Adam P.; Coeytaux, Remy R.; McDuffie, Jennifer; Duan-Porter, Wei; Sharma, Poonam; Mennella, Hillary; Nagi, Avishek; Williams, John W.
Highlights: Yoga has been proposed as a treatment modality for non-specific low back pain in numerous randomized clinical trails. Three good quality systematic reviews have been conducted on randomized clinical trials determining the effectiveness of yoga for low back pain. Evidence suggests benefit of yoga in midlife adults with non-specific low back pain for short- and long-term pain and back-specific disability. The effects of yoga for health-related quality of life, well-being and acute low back pain are uncertain. Abstract: Objective: Yoga is being increasingly studied as a treatment strategy for a variety of different clinical conditions, including low back pain (LBP). We set out to conduct an evidence map of yoga for the treatment, prevention and recurrence of acute or chronic low back pain (cLBP). Methods: We searched Medline, Cochrane Database of Systematic Reviews, EMBASE, Allied and Complementary Medicine Database andClinicalTrials.gov for randomized controlled trials (RCT), systematic reviews or planned studies on the treatment or prevention of acute back pain or cLBP. Two independent reviewers screened papers for inclusion, extracted data and assessed the quality of included studies. Results: Three eligible systematic reviews were identified that included 10 RCTs ( n = 956) that evaluated yoga for non-specific cLBP. We did not identify additional RCTs beyond those included in the systematic reviews. Our search ofClinicalTrials.gov identified one small ( n = 10) unpublished trial and one large ( n = 320) planned clinical trial. The most recent good quality systematic review indicated significant effects for short- and long-term pain reduction ( n = 6 trials; standardized mean difference [SMD] −0.48; 95% CI, −0.65 to −0.31; I 2 = 0% and n = 5; SMD −0.33; 95% CI, −0.59 to −0.07; I 2 = 48%, respectively). Long-term effects for back specific disability were also identified ( n = 5; SMD −0.35; 95% CI, −0.55 to −0.15; I 2 = 20%). No studies were identified evaluating yoga for prevention or treatment of acute LBP. Conclusion: Evidence suggests benefit of yoga in midlife adults with non-specific cLBP for short- and long-term pain and back-specific disability, but the effects of yoga for health-related quality of life, well- being and acute LBP are uncertain. Without additional studies, further systematic reviews are unlikely to be informative.